NLRP3 Is Involved in the Maintenance of Cerebral Pericytes - Quan, Wenqiang; Luo, Qinghua; Tang, Qiqiang; Furihata, Tomomi; Li, Dong; Fassbender, Klaus; Liu, Yang (Frontiers in Cellular Neuroscience, 2020)
Pericytes play a central role in regulating structure and function of capillaries in the brain. However, molecular mechanisms which drive pericyte proliferation and activation are unclear. In our study, we immunostained NLRP3-deficient and wild-type littermate mice and observed that NLRP3 deficiency reduced PDGFRβ-positive pericytes and collagen type IV immunereactive vasculature in the brain. In Western blot analysis, PDGFRβ and CD13 proteins in isolated cerebral microvessels from NLRP3-deficient mouse brain was decreased. We further treated cultured pericytes with NLRP3 inhibitor, MCC950, and demonstrated that NLRP3 inhibition attenuated cell proliferation but did not induce apoptosis. NLRP3 inhibition also decreased protein levels of PDGFRβ and CD13 in cultured pericytes. On the contrary, treatments with IL-1β, the major product of NLRP3-contained inflammasome, increased protein levels of PDGFRβ and CD13 in cultured cells. The alteration of PDGFRβ and CD13 protein levels was correlated with phosphorylation of AKT. Inhibition of AKT reduced both protein markers and abolished the effect of IL-1β activation in cultured pericytes. Thus, NLRP3 activation might be essential to maintain healthy pericytes in the brain through phosphorylating AKT. Administration of NLRP3 inhibitors in clinical therapies has a potential to damage pericytes in the brain.